Ideas from the Political, Economic and Social System of the Polish People’s Party in the Years 1989–2011 - Kotulewicz, Karolina (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article presents the evolution of the political thought of the Polish People’s Party (PSL) after 1989 and up until the parliamentary elections of 2011. The main issues to be tackled are the concept of the state’s political system as well as its economic model and social policy. PSL’s multiyear traditions and its values, among which family and religious values hold an important place, influence the party’s views. The party is active on the legislative and – through the creation of coalition governments – executive levels.